Performance analysis of single and double basin-inclined solar water distillation systems with and without black-fleece wick - Aybar, Hikmet S.; Irani, Foad; Arslan, Mevlut (Desalination Publ, 2016)
The aim of this study is to design and to test the double basin-inclined solar water distillation (DB-ISWD) system and compare it with the single basin-inclined solar water distillation (SB-ISWD) system under the northern Cyprus environmental conditions. The SB-ISWD and the DB-ISWD systems have the ability to produce both freshwater and hot water at the same time. In the SB-ISWD system, the feeding water falls down on the bare plate (BP) through the distribution pipe. The DB-ISWD system has two sections: the lower section and the upper section. In the lower section, the feeding water falls down on the BP through distribution pipe. In the upper section, the feeding water falls down on the transparent glass through distribution pipe. These systems are tested by two variants: BP and with black-fleece wick. It is observed that both systems show higher production rate of freshwater when the black-fleece wick is used. Also, the hot water production by both systems is hot enough for domestic appliances. In comparison of these two systems, the amount of condensate water and hot water produced by the DB-ISWD system is more than that of the SB-ISWD system.
Keywords: Solar distillation; Solar hot water; Wick